2016
DOI: 10.1007/s00247-016-3735-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous guided biopsy for diagnosing suspected primary malignant bone tumors in pediatric patients: a safe, accurate, and cost-saving procedure

Abstract: Percutaneous biopsy is a valid alternative to open biopsy for diagnosing pediatric and young adult primary malignant bone tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
18
3
Order By: Relevance
“…Historically, an incisional (open) biopsy has been the preferred method for tumor tissue sampling in bone sarcomas. However, a percutaneous (needle) biopsy can also provide adequate tumor material to effectively establish the diagnosis of either OS or EWS . Historically, the small amount of tumor material obtained for research purposes has been one of the limitations to performing percutaneous biopsies in patients with bone sarcomas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, an incisional (open) biopsy has been the preferred method for tumor tissue sampling in bone sarcomas. However, a percutaneous (needle) biopsy can also provide adequate tumor material to effectively establish the diagnosis of either OS or EWS . Historically, the small amount of tumor material obtained for research purposes has been one of the limitations to performing percutaneous biopsies in patients with bone sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, a percutaneous (needle) biopsy can also provide adequate tumor material to effectively establish the diagnosis of either OS or EWS. [2][3][4][5] Historically, the small amount of tumor material obtained for research purposes has been one of the limitations to performing percutaneous biopsies in patients with bone sarcomas. We have developed a multi-Abbreviations: EWS, Ewing sarcoma; IRB, institutional review board; OS, osteosarcoma; PDX, patient-derived tumor xenograft; TTF, time to tumor formation; US, ultrasound disciplinary team approach to establish an adequate cancer diagnosis and to develop patient-derived tumor xenografts (PDXs) using percutaneous biopsies in patients with bone sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications have reported that CT-guided percutaneous core-needle biopsy is a well-established technique and is effective for the initial diagnosis of musculoskeletal lesions, with a measured diagnostic yield ranging between 70 and 89% and a reported accuracy between 61 and 98% [211]. These results confirm the high sensitivity of CT-guided percutaneous needle biopsy for the diagnosis of bone tumors through the use of a minimally invasive procedure, which is associated with cost savings and fewer biopsy complications than open surgical biopsy [6, 7, 1014]. However, the disadvantage of this guided biopsy method is that metabolically active lesions without distinctive morphology may not be reliably assessable by CT-guided biopsy, and the false-negative biopsy rate of such lesions may be substantially higher with CT-guided biopsy [15].…”
Section: Introductionmentioning
confidence: 71%
“…In our cohort no tumor dissemination along the needle track is found. It is also quite rare in previous studies 9, 13,19 and almost all the reports are related with nephroblastoma 18,21,22 and the prognosis is generally quite good after chemotherapy and excision. Another earlier research on biopsy of renal tumors suggest posterolateral entries to confine tumor soilage instead of peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies, reported complications included pain, intra-abdominal infection, pneumothorax, hematuria, and hemorrhage 8,9,13,[16][17][18][19][20] . Post-biopsy bleeding including intra-tumoral hematoma is the most common.…”
Section: Discussionmentioning
confidence: 99%